2017
DOI: 10.1016/j.cellimm.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides derived from Ganoderma lucidum fungus mycelia ameliorate indomethacin-induced small intestinal injury via induction of GM-CSF from macrophages

Abstract: Non-steroidal anti-inflammatory drugs often cause ulcers in the human small intestine, but few effective agents exist to treat such injury. Ganoderma lucidum Karst, also known as "Reishi" or "Lingzhi", is a mushroom. We previously reported that a water-soluble extract from G. lucidum fungus mycelia (MAK) has anti-inflammatory effects in murine colitis induced by trinitrobenzene sulfonic acid, and induction of granulocyte macrophage colony-stimulating factor (GM-CSF) by MAK may provide anti-inflammatory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Recently, edible mushrooms have attracted researchers' attention due to their diverse pharmacological effects and minimal adverse effects. For example, Ganoderma lucidum alleviates intestinal damage induced by indomethacin in mice ( 43 ) and Hericium erinaceus improves testicular damage via its antioxidative effects and regulation of the GPR41/43 receptor in UC rats and Caco-2 cells ( 44 ). Based on the immunomodulatory and anti-inflammatory effects of GI reported previously ( 7 ), the present study successfully confirmed its protective effect against UC in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, edible mushrooms have attracted researchers' attention due to their diverse pharmacological effects and minimal adverse effects. For example, Ganoderma lucidum alleviates intestinal damage induced by indomethacin in mice ( 43 ) and Hericium erinaceus improves testicular damage via its antioxidative effects and regulation of the GPR41/43 receptor in UC rats and Caco-2 cells ( 44 ). Based on the immunomodulatory and anti-inflammatory effects of GI reported previously ( 7 ), the present study successfully confirmed its protective effect against UC in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin (10 mg/kg) subcutaneous injection in mice increased intestinal permeability and induced ulcers 24 h post administration [135]. These consequences have also been observed 24 h after oral indomethacin administration [137,138] in mice (10 mg/kg) and rats (15 mg/kg). Gut permeability increased over the first hours after a single indomethacin gavage in rats (20 mg/kg) and returned to normal four days post treatment [139].…”
Section: Enteropathy Modelsmentioning
confidence: 99%
“…Our results proved the beneficial effects of GLP on the symptoms of colitis, which were depicted when assessing the survival rate, body weight loss, colon length, histopathological scores, and DAI score ( Figure 1 ). Recent results showed that polysaccharides derived from G. lucidum fungus mycelia ameliorate indomethacin-induced small intestinal injury by induction of granulocyte macrophage colony-stimulating factor (GM-CSF) from macrophages [ 45 ]. However, the result of our study showed that GLP had no effects on the populations of macrophage and the neutrophils in colonic LP in mice with DSS-induced acute colitis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%